NMR Spectroscopy in Inorganic Chemistry (2nd Edition) - Iggo, Jonathan A.; Luzyanin, Konstantin V. (Oxford Chemistry Primers, 2020)
The renowned Oxford Chemistry Primers series, which provides focused introductions to a range of important topics in chemistry, has been refreshed and updated to suit the needs of today's students, lecturers, and postgraduate researchers. The rigorous, yet accessible, treatment of each subject area is ideal for those wanting a primer in a given topic to prepare them for more advanced study or research. Moreover, cutting-edge examples and applications throughout the texts show the relevance of the chemistry being described to current research and industry. This new edition of this book has been extensively updated to include worked examples, problems, self-test questions, and interactive online questions encouraging active learning and promoting a deeper understanding. With a concise and accessible introduction to predicting NMR spectra and expanded sections on quadrupolar nuclei, this excellent introductory text will help students get to grips with the basics before building on that understanding through diagrammatic content to explain the more challenging concepts.